Supporting knowledge construction in elementary engineering design. Issue 4 (25th March 2019) - Wendell, Kristen B.; Andrews, Chelsea J.; Paugh, Patricia
Abstract: Engineering design learning experiences are increasingly offered as part of elementary school, but research on how to support young learners' knowledge construction during classroom engineering is still preliminary. Questions remain about how classroom supports can make engineering thinking visible so that students build engineering knowledge along with engineering products . We report results from a case study of an 11‐day teaching experiment in two elementary classrooms. With the classroom teachers, we guided fourth and fifth graders to document their design iterations with a digital notebooking tool, participate in whole‐class design talks, and create and exhibit posters with "stomp rocket" design recommendations. We conducted a microethnographic analysis of students' interactions with these notebooking, talk, and poster tools. Our findings characterize how students constructed engineering design knowledge through the discourse of sense‐making about rocket phenomena, decision‐making for specific rocket iterations, and representation‐making for external audiences. These results have implications for elementary engineering instruction: it appears productive for learning to structure whole‐class design talks around representations of sequences of prototypes over time, rather than focusing only on current or best physical prototypes, and to structure engineering curriculum units so that they culminate with student‐generated sets of design recommendations, rather than single design solutions.